Trigonometry - Hayden, Jerome D.; Hall, Bettye C.; Fair, Jan; Kalin, Robert; Bragg, Sadie C.; Corbitt, Mary Kay; Fabricant, Mona (Englewood Cliffs, New Jersey : Prentice-Hall, 1993)
Trigonometry, like algebra and geometry, is considered a language of mathematics, and mathematics is a vital part of your life. Changes in society and the use of technology require that you have a strong background in mathematics .
Part 1. Trigonometric Functions -- Part 2. Graphing Trigonometric Functions -- Part 3. Right Triangle Trigonometry and Basic Identities -- Part 4. Oblique Triangles -- Part 5. Trigonometric Identities -- Part 6. Inverse Trigonometric Functions -- Part 7. Complex Numbers -- Part 8. Exponential and Logarithmic Functions -- Part 9. Sequences and Series .
Includes index.
Keywords: TRIGONOMETRY